The Nexus Between Human Resource Management Practices and Service Recovery Performance in Takaful Insurance Industry in Pakistan: The Mediating Role of Employee Commitment - Mao, Jie; Siyal, Saeed; Javed Ahmed, Munawer; Ahmad, Riaz; Xin, Chunlin; Qasim, Samina (Frontiers in Psychology, 2022)
Service recovery performance is very important for the takaful insurance industry for maintaining and attracting new clients which in turn serves as a competitive advantage for the survival and continued future of the businesses. If the insurance sector could not be able to maintain the service recovery performance, then the competitive advantage of the organizations could be decayed. Therefore, under the theoretical foundation of equity theory and resource-based theory, this research has investigated the link between human resources management practices (HRMP) (such as human capital, training, job description, teamwork, empowerment, and rewards) and service recovery performance (SRP) directly and indirectly through the employee commitment. By using a convenient sampling technique data was collected from the employees working in the Takaful industry in Pakistan to empirically test the proposed hypotheses and validate the findings. Using cross research design and quantitative research approach. The Structural Equation Modeling (SEM) had presented the positive relationship between HRM practices and SRP. On the other, employee commitment had also mediated this relationship. As employee commitment is significantly mediate in among most of the HRMP, therefore this is considered to be big contribution of the study in the context of Pakistan. Based on these findings, the current study had a several important implications for the practitioners and readers.